New Challenges in Economic and Business Development – 2023: Recovery and Resilience: PROCEEDINGS; (15th International Scientific Conference, May 11-13, 2023, Riga, University of Latvia) - (:unkn) unknown (University of Latvia, 2023)
This year's conference is devoted to the challenges related to the recovery and resilience. Recovery and Resilience Facility is an important component of the European recovery plan (the Next Generation EU) which aims to overcome the economic and social effects of the Covid-19 pandemic and ensure better resilience of the EU Member States in the future. The objective of the conference was to provide a platform/opportunity for scholars, researchers and professionals from different disciplinary backgrounds to meet, exchange ideas, findings, research results and discuss challenges and prospects for economic and business development.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Business and economics